Influence of Japan’s 2004 postgraduate training on ophthalmologist location choice, supply and distribution - Rie Sakai-Bizmark; Rei Goto; Shusuke Hiragi; Hiroshi Tamura (BMC Medical Education, 2018)
Abstract Background Highly-competent patient care is paramount to medicine. Quality training and patient accessibility to physicians with a wide range of specializations is essential. Yet, poor quality of life for physicians cannot be ignored, being detrimental to patient care and leading to personnel leaving the medical profession. In 2004, the Japanese government reformed postgraduate training for medical graduates, adding a 2-year, hands-on rotation through different specialties before the specialization residency was begun. Residents could now choose practice location, but it sparked concerns that physician distribution disparities had been created. Japanese media reported that residents were choosing specialties deemed to offer a higher quality of life, like Ophthalmology or Dermatology, over underserved areas like Obstetrics or Cardiology. To explore the consequences of Japan’s policy efforts, through the residency reform in 2004, to improve physician training, analyzing ophthalmologist supply and distribution in the context of providing the best possible patient care and access while maintaining physician quality of life. Methods Using secondary data, we analyzed changes in ophthalmologist supply at the secondary tier of medical care (STM). We applied ordinary least-squares regression models to ophthalmologist density to reflect community factors such as residential quality and access to further professional development, to serve as predictors of ophthalmologist supply. Coefficient equality tests examined predictor differences before and after 2004. Similar analyses were conducted for all physicians excluding ophthalmologists (other physicians). Ophthalmologist coverage in top and bottom 10% of STMs revealed supply inequalities. Results Change in ophthalmologist supply was inversely associated with baseline ophthalmologist density before (P < .01) and after (P = .01) 2004. Changes in other physician supply were not associated with baseline other physician density before 2004 (P = 0.5), but positively associated after 2004 (P < .01). Inequalities between top and bottom 10% of ophthalmologist supply in STMs were large, with best-served areas maintaining roughly five times greater coverage than least-served areas. However, inequalities gradually declined between 1998 and 2012. Conclusions Ophthalmologist supply increased both before and after the 2004 reform, yet contrary to media reports, proceeded at a lesser rate than supply increases for other physicians. After 2004, geographical disparities decreased for ophthalmologists, while increasing for other physicians.